Pengaruh Lingkungan Kerja dan Motivasi terhadap Kinerja Karyawan Perusahaan Daerah Air Minum Kabupaten Kapuas - Yuni Ra Chandraningrum; M. Nodin Ideram; Setio Utomo (JURNAL BISNIS DAN PEMBANGUNAN, 2015)
This study aims to examine and analyze the effect of partial and simultaneous work environment and motivation on employee performance taps Kapuas. In addition to the basic tasks as channeling water, PDAM Kabupaten Kapuas required to pay more attention to aspects of its human resources to create professional employees, strong, agile, intelligent and forward-looking. One of the factors that can affect the performance of the employee is to create a good working environment and motivation.The research was conducted on PDAM Kapuas. This study uses a quantitative approach. The type of research is research explanation (explanatory research). Population and sample in this study were employees of PDAM Kabupaten Kapuas many as 75 people. Technical data collection with documentation, questionnaires, interviews, observation. Variables examined with Likert scale. Questionnaires first tested the validity and reliability test. Data processing software SPSS version 21.0 was analyzed with descriptive statistical analysis and hypothesis testing with multiple linear regression.The conclusion of this study is no partial effect the working environment of 21.6% and 71.4% motivation on employee performance PDAM Kabupaten Kapuas. Simultaneously influence the work environment and motivation on employee performance PDAM Kabupaten Kapuas 47.5%. The variable most dominant influence on employee performance is variable motivation.Keywords: Work Environment, Motivation, Employee Performance